Moral values and instrinsic elements depicted in the novel entitled black notice by patricia cornwell - Nelly Novida; Tahrun Tahrun; Artanti Puspita Sari (Global Econedu, 2021)
Great value and culture of Indonesian people that very popular around the world. The multidimensional crisis in Indonesia is currently very worrying, especially the moral crisis. The moral crisis also occurs in the world of education. So this study aimed to reveal the moral value and instrinsic elements form the novel Black Notice by Patricia Cornwell relate to people from different environment by interview. The data of the research were gained through triangulation technique taken from novel, book review and interview which are analysed with desrcriptive qualitatively afterwards,and describe the condition and relation which are held and process still going. The result of the research found some moral values and instrinsic elements include the novel Black Notice by Patricia Cornwell by using Socio Cultural Historical Approach and Biographical Approach.